O nascimento de um índio na rua do Ouvidor: José de Alencar Best-seller - Carneiro, Andreia Ferreira Alves (2012)
To understand the process of canonization of a writer you need to look again at that time lived. In this study, we try to understand the mechanisms used by José de Alencar, in the nineteenth century, through the publication of his first serials Cinco minutes, O Guarany e A viuvinha in order to hold the attention of your public reader. This public that later consecrated him as great name of Brazilian Literature. Since Brazil had few readers as the author of O Guarany attracted a larger number of readers? José de Alencar would be the first Brazilian Best-seller? Try to understand also how literary criticism saw these new writers and the contrasts were between the reception of readers and critics in this time. To help this research, we observed various opinions of scholars, among them Luis Viana Filho, Muniz Sodré, Antonio Candido, José Alcides Ribeiro, Oscar Mendes and José de Alencar himself with his autobiographical book, Como e porque sou romancista.